The Skill Profile of Pre-Service Science Teachers In Writing Strem-Based (Science-Technology-Religion-Engineering-Mathematics) Science Teaching Materials - Wahyuni Handayani; Tri Wahyu Agustina; Muhammad Ghilman Firdaus (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
This study aims to identify the profile of STREM-based science writing skills in pre-service science teachers. The study was done using a descriptive method through a study of STREM-based science teaching materials documentation written by the pre-service science teachers. The target population is the seventh-semester students. Fifty people who are enrolled in the elective course of Integrated Science Learning were selected through Purposive Sampling. Performance assessment of the STREM-based science teaching materials was done using an analytical rubric with a score of 1-4 on the aspect of pedagogic, content, and context. Determination of inter-rater reliability was taken from 25 random samples of teaching materials and correlated their scores using Pearson's correlation. The inter-rater reliability score obtained is 0.938 in all aspects of teaching materials; 0.690 in the pedagogic aspect; 0.976 in the aspect of content; and 0.921 in the context aspect. The score of the teaching materials is then converted in the form of a percentage and interpreted based on certain criteria. The average score of pre-service science teachers' writing skills was 53.3% in the "good" criteria. The writing quality of teaching materials has not yet met the expected criteria from the pedagogic, content, and context aspects. Thus, it is important to develop appropriate learning strategies to improve the writing skills of STREM-based science teaching materials for pre-service science teachers.